Storage Stability of High Fiber Snack Bar - Ivana Aprilia Pratiwi; Varongsiri Kemsawasd; Thunnalin Winuprasith (GHMJ (Global Health Management Journal), 2019)
Background: Recently, there has been considerable interest in increasing the dietary fiber content in food products because of inadequate dietary fiber consumption when considering the daily recommended intake. To increase dietary fiber intake, dietary fiber fortified foods are recommended. This study aimed to develop a high fiber snack bar (HFSB) using a combination of Jerusalem artichoke powder (JAP) and low-fat desiccated coconut (LFDC) as sources of dietary fiber. Methods: The changes in physicochemical and microbiological properties, and sensory acceptability were measured during storage at 35 oC and 45 oC for 12 weeks. Therefore, the shelf-life of the products was calculated by Q10 test. Results: The HFSB had a higher L* value (lightness) than control (C) due to the addition of LFDC. Total dietary fiber of the HFSB was approximately 3.7 times higher than that of the C formula. The L*, a*, and b* values of both C and HFSB were statistically significant different (p<0.05) after storage. The total color different (ï¿¿E) values of the HFSB were higher than those of the C formula due to inulin from JAP, which participated in the Maillard reaction. During storage, the moisture content (MC) and water activity (aw) of the HFSB remained more stable compared to those of the C due to the water-holding capacity of the fiber used. The aw of the C and HFSB during storage were in the range of 0.57 to 0.60 and 0.53 to 0.57, respectively. Those ranges should be stable against microbial growth. Higher storage temperature would increase the TBARS values and decrease the pH (p<0.05) of the C and HFSB due to deterioration. In terms of shelf-life calculation, the C and HFSB snack bar could be kept in metalized polyester at 30 oC for 11 weeks. Conclusion: The JAP and LFDC exhibited great potential for use as fiber ingredients. Although the JAP and LFDC influenced the physicochemical properties and sensory acceptability, the shelf-life of both C and HFSB was comparable. Therefore, further studies should be conducted to extend the shelf-life of the formulated snack bar. Keywords: Snack bar, High fiber, Jerusalem artichoke, Low-fat desiccated coconut, Shelf-life Received: 8 May 2019 Reviewed: 14 June 2019 Revised: 26 June 2019 Accepted: 19 July 2019 DOI: 10.35898/ghmj-33585